PENGARUH KOMUNIKASI, MOTIVASI, DAN LINKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. METATANI PALMA ABADI KABUPATEN SELUMA - Melda Yunita; Eno Edi Pratama (Yayasan Insani Mandiri Santani, 2023)
This study aims to determine the effect of communication, motivation and work environment on the performance of employees of PT.Metatani Palma Abadi District Ulu Talo Seluma Regency. The population in this study were all employees of PT.Metatani Palma Abadi District Ulu Talo Seluma Regency in Division 3 using the Total Sampling method. With the number of respondents in this study were 175 people. In this study using data collection methods by means of observation, interviews and questionnaires. The data that has been collected is then processed using Test Instruments, Analysis of Respondents' Responses, Classical Assumption Test, Multiple Linear Analysis, Coefficient of Determination (R2) and Hypothesis Test. Based on the results of Multiple Linear Regression Analysis, the equation Y = 5.664 + 0.268 (X_1) + 0.131 (X2) + 0.221 (X3) is obtained. The results of the research and the hypothesis show that the Communication variable (X1) shows t_hit> t_ (α / 2) (3,723> 1,973) and (sig α = 0,000 <0.050), Motivation (X2) shows t_hit> t_ (α / 2) (2.191 > 1.973) and (sig α = 0.030 <0.050), the Work Environment (X3) shows t_hit> t_ (α / 2) (2,966> 1,973) and (sig α = 0.003 <0.050). The results of the F test show a significant value of F, namely (0.000 <0.050) and the value of Fcount> Ttable, namely (24.541> 3,895). From the results of data management, it can be concluded that all independent variables, namely communication, motivation, and work environment have a significant effect on the devendent variable, namely employee performance. Keywords: Communication, Motivation, and Work Environment, Employee Performan.